Integrative analyses reveal RNA regulatory network in Ti particles induced inflammation. (1st September 2021) - Jiang, Yonghui; Ma, Huanzhi; Zhang, Qin; Shi, Jun; Gao, Yutong; Sun, Chengliang; Zhang, Wei
Introduction Wear particles induced inflammatory osteolysis is the most important initiating factors in the mechanism of aseptic loosening. However, the molecular network changes in this process remain largely elusive.Methods Here, we performed whole transcriptome analysis using Ti particles induced RAW264.7 cell model to identify specific genes and pathways.Results Sequencing results totally identified 159 mRNAs, 96 lncRNAs, 31 circRNAs, and 12 miRNAs were significantly differently expressed. Of these, we selected two of each RNA for qRT-PCR validation and the results were highly consistent with the RNA-seq data. GSEA analysis shows that upregulated gene sets were related to the three classical inflammation pathway, cytokine–cytokine receptor interaction, TNF, and NF-kappa B signaling pathway. The enriched genes included not only IL-1β and TNF- α, which were independently verified before sequencing, but also other inflammatory osteolysis-related genes such as Mmp9, Fas, and Ccl2. Co-differentially expressed RNAs were employed to construct the ceRNA co-regulatory network.Conclusion : The results revealed that 4 lncRNAs and 2 circRNAs formed a regulatory network to simultaneously regulate miR-3065-3p targeting Myo18a . The present study helps to comprehensively understand the molecular mechanisms and regulatory interaction networks during early inflammatory response.